Belgian population norms for the EQ-5D-5L, 2013 and 2018. (30th September 2020) - Van Wilder, L; De Smedt, D; Beutels, P; Cleemput, I; Bilcke, J; Speybroeck, N; Van der Heyden, J; Van Oyen, H; Charaffedine, R; Devleesschauwer, B
Abstract: Background: Health-related quality of life outcomes are increasingly used to monitor population health and health inequalities, and to assess the (cost-)effectiveness of health interventions. The EQ-5D-5L has been included in the Belgian Health Interview Survey (BHIS), providing a new source of population-based self-perceived health status information. The aim of this study is to estimate Belgian population norms for the EQ-5D-5L by sex, age, and region, and to analyse its association with educational attainment. Methods: The BHIS 2013 and 2018 provided EQ-5D-5L data for a nationally representative sample of the Belgian population. The dimension scores and index values were analysed using logistic regression and linear regression, respectively, taking into account the survey design. Results: The majority of respondents reported problems of pain/discomfort, while over a quarter reported problems of anxiety/depression in both surveys. The average index value was 0.81 in 2013 and decreased significantly to 0.79 in 2018. Women reported more problems on the dimensions, but particularly on anxiety/depression and pain/discomfort, resulting in significantly lower index values. Problems with mobility, self-care, and usual activities showed a sharp increase after the age of 80 years. Consequently, index values decreased significantly by age. Lower education was associated with a higher prevalence of problems for all dimensions except pain/discomfort in 2013 and anxiety/depression in 2018, and with a significantly lower index value. Conclusions: This paper presents the first nationally representative Belgian population norms using the EQ-5D-5L. Inclusion of the EQ-5D in future surveys will allow monitoring over time of self-reported health, disease burden, and health inequalities. Key messages: This study is the first to provide Belgian population norms for the EQ-5D-5L and consequently increases the evidence base regarding country-specific population norms. Our results help policy makers in understanding and monitoring the self-perceived health status of the Belgian population according to age, gender, and educational attainment.